2018
DOI: 10.1152/ajpregu.00239.2017
|View full text |Cite
|
Sign up to set email alerts
|

Acyloxyacyl hydrolase modulates pelvic pain severity

Abstract: Chronic pelvic pain causes significant patient morbidity and is a challenge to clinicians. Using a murine neurogenic cystitis model that recapitulates key aspects of interstitial cystitis/bladder pain syndrome (IC), we recently showed that pseudorabies virus (PRV) induces severe pelvic allodynia in BALB/c mice relative to C57BL/6 mice. Here, we report that a quantitative trait locus (QTL) analysis of PRV-induced allodynia in F2 progeny identified a polymorphism on chromosome 13, rs6314295 , significantly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 87 publications
(91 reference statements)
6
36
0
Order By: Relevance
“…Although lipidomics showed that sacral spinal cords of female wild type mice contained more AA-containing PE than AOAH-deficient mice, it was unclear whether AOAH could directly modulate the sequestration of AA among CNS phospholipids. Microarray analyses showed that variant 3 of human AOAH (hAOAH3) was highly expressed in the CNS compared to other hAOAH variants [ 5 , 11 , 26 ]. We generated a recombinant lentivirus encoding hAOAH3 and, after confirming that HEK293 cells lack AOAH expression by immunoblotting (not shown), transduced HEK293 cells with AOAH3 or lacZ to obtain the 293 lenti-hAOAH3 and 293 lenti-lacZ cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although lipidomics showed that sacral spinal cords of female wild type mice contained more AA-containing PE than AOAH-deficient mice, it was unclear whether AOAH could directly modulate the sequestration of AA among CNS phospholipids. Microarray analyses showed that variant 3 of human AOAH (hAOAH3) was highly expressed in the CNS compared to other hAOAH variants [ 5 , 11 , 26 ]. We generated a recombinant lentivirus encoding hAOAH3 and, after confirming that HEK293 cells lack AOAH expression by immunoblotting (not shown), transduced HEK293 cells with AOAH3 or lacZ to obtain the 293 lenti-hAOAH3 and 293 lenti-lacZ cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research showed that administration of an EP1 antagonist alleviated rat cystitis and modulated pain [ 34 , 35 ]. To clarify the potential consequence of dysregulated AA homeostasis in the spontaneous pelvic pain phenotype of AOAH-deficient mice, we next examined the impact of EP1 antagonist ONO-8711 by quantifying pelvic mechanical allodynia in response to von Frey filaments applied to the pelvic region [ 5 ]. Briefly, 5 filaments of increasing stiffness (i.e., increasing applied force) were applied to the pelvic region ten times each and expresses at the percent responses to each stimulus force.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when LPS is transferred and bound to MD-2, the fatty acyl chains are less accessible, decreasing AOAH's ability to deacylate LPS and reduce TLR4 activation (Gioannini et al 2007). Whether the female reproductive tract has the capacity to locally detoxify LPS remains unknown though recently, the importance of AOAH in the lung (Zou et al 2017), urinary tract (Yang et al 2017) and colonic dendritic (Janelsins et al 2014) cells has been demonstrated.…”
Section: Detoxification Of Lps By Acyloxyacyl Hydrolasementioning
confidence: 99%